Synthesis of a library of tricyclic azepinoisoindolinones - Miller, Bettina; Mao, Shuli; Rosenker, Kara M. George; Pierce, Joshua G.; Wipf, Peter (Beilstein Journal of Organic Chemistry, 2012)
Hydrozirconation of 1-hexyne, the addition to in situ prepared N-acyliminium species, and ring-closing metathesis (RCM) were key steps in the preparation of a tricyclic isoindolinone scaffold. An unusual alkene isomerization process during the RCM was identified and studied in some detail. Chemical diversification for library synthesis was achieved by a subsequent alkene epoxidation and zinc-mediated aminolysis reaction. The resulting library products provided selective hits among a large number of high-throughput screens reported in PubChem, thus illustrating the utility of the novel scaffold.
Keywords: chemical diversity; epoxide aminolysis; hydrozirconation; isoindolinones; metathesis; N-acyliminium ion